The Effect of the Linking Unit on the Electronic and Magnetic Interactions in Copper(II) Porphyrin Dimers Linked by Metal Ions - Jordan L. Appleton; Nolwenn Le Breton; Sylvie Choua; Romain Ruppert (Inorganics, 2024)
The syntheses of a series of copper(II) porphyrins and their dimers linked by palladium(II) or platinum(II) are reported. Their electronic properties and their magnetic properties were studied. In particular, the effect of the linking unit on these properties was evaluated. It was discovered that three factors influence the electronic and magnetic interactions between the two metalloporphyrins: the nature of the linking metal ion, the nature of the external coordination site of the porphyrin, and also the nature of the metal ion present in the central core of the aromatic macrocycle.